Defining outcomes following congenital diaphragmatic hernia using standardised clinical assessment and management plan (SCAMP) methodology within the CDH EURO consortium. (August 2018) - IJsselstijn, Hanneke; Breatnach, Cormac; Hoskote, Aparna; Greenough, Anne; Patel, Neil; Capolupo, Irma; Morini, Francesco; Scharbatke, Horst; Kipfmueller, Florian; Ertresvag, Kjetil; Kraemer, Ulrike; Braguglia, Annabella; et al.
Abstract Treatment modalities for neonates born with congenital diaphragmatic hernia (CDH) have greatly improved in recent times with a concomitant increase in survival. In 2008, CDH EURO consortium, a collaboration of a large volume of CDH centers in Western Europe, was established with a goal to standardize management and facilitate multicenter research. However, limited knowledge on long-term outcomes restricts the identification of optimal care pathways for CDH survivors in adolescence and adulthood. This review aimed to evaluate the current practice of long-term follow-up within the CDH EURO consortium centers, and to review the literature on long-term outcomes published from 2000 onward. Apart from having disease-specific morbidities, children with CDH are at risk for impaired neurodevelopmental problems and failure of educational attainments which may affect participation in society and the quality of life in later years. Thus, there is every reason to offer them long-term multidisciplinary follow-up programs. We discuss a proposed collaborative project using standardized clinical assessment and management plan (SCAMP) methodology to obtain uniform and standardized follow-up of CDH patients at an international level.